Tracking the signature of low symmetry environments in the XAS K pre-edge. (May 2016) - Hunault, M; Vercamer, V; Haverkort, M W; Arrio, M-A; Brouder, C; Calas, G; Juhin, A
Abstract: For Co-containing crystalline compounds measured by XAS, the influence of the local symmetry on the K pre-edge features is studied using advanced Ligand Field Multiplet (LFM) calculations, which accurately take into account the p-d hybridization. The LFM theory is used to calculate the K pre-edge spectra of Co 2+ in various environments and the absolute intensities of electric-quadrupole and -dipole transitions involved in the pre-edge. This enables to reproduce the spectra for cubic (Oh, Td ) and lower symmetries (C4v, D3h ), and allows quantitative derivation of the local p-d mixing.